Perceptions of accompanents about the verbal communication of the nursing team in emergency (Research, Society and Development, 2020)
Communication is the main way to alleviate the emotional suffering of patients and their families in emergency care units. In this sense, the question is: what are the perceptions of the patients' companions regarding verbal communication skills of nursing professionals? Are the companions satisfied with the information offered at the hospital emergency and emergency unit? Can these identify verbal communication failures during the care offered to the patient? This study aims to verify the perception of the caregivers of sick people in the hospital emergency department about the dialectic with the nursing team, through analysis of the scientific literature. This is an integrative review of the literature, carried out with publications in the VHL in full article format available in Portuguese and English between 2008-2018. The research occurred the DeCS: communication in health and nursing, and irregular keyword: companion. Excluded were works that were not free, duplicated and that in their title and abstract did not contemplate the content studied. The perception of the companions about the verbal communication with the nursing team is not satisfactory, because, there are several studies that point out faults on the relation of the team with the companion, thus compromising the necessary dialogue between both to contribute with the care provided to the patients. Therefore, it is necessary that studies directed to this theme be carried out to enrich the scientific literature, providing, more information about the content so that a more critical and reflective look is given, and, therefore, an improvement in the quality of care provided by the nursing team.